A-33 Criteria For Determining Clinical Recovery From Concussion: A Preliminary Survey Of Sports Neuropsychologists. (13th July 2022) - Moser, R S; Choi, D M; Mayer, B
Abstract: Purpose: To arrive at a consensus of best practices currently employed by sports neuropsychologists regarding specific criteria for determining concussion recovery. Methods: A survey was sent to 120 sports neuropsychologists listed in a public membership directory of the Sports Neuropsychology Society. The survey included demographic, Likert-style, and multiple-choice questions regarding the importance of given criteria in determining concussion recovery for youth (up to age 18) or adult (18+ years). Results: A sample of 22 participants (95% White, 59% male, 68% working with youth and adults, 45% seeing ≥50 patients yearly, 86% ≥10 years of experience) was obtained. The two highest rated criteria for youth and adults were: 1) symptom-free with exercise, and 2) back to work/school without symptoms or accommodations. The two lowest rated criteria were: 1) physician exam without concerns, and 2) opinions from another healthcare professional. Of those who treat adults, 71% reported 1 week symptom free is sufficient. For youth, 63% rated ≥1 week, 31% rated 2–3 weeks, and 6% rated ≥1 month is preferred. Conclusions: Most respondents have worked with youth and adult athletes for at least 10 years. Responses were mostly consistent regarding importance of the various surveyed criteria. There may be a tendency to wait for longer symptom-free periods for youth. Interestingly, the opinions of another health care professional or physician were less important than all other criteria in the survey. The two most important criteria appear to be resolution of symptoms during physical exertion and return to functional activities without symptoms or accommodations.